How congruent are parent reports on 3–4-year-old children’s language skills with other sources of data? - Tulviste, Tiia; Schults, Astra (Frontiers in Psychology, 2023)
Background Parental report measures such as the MacArthur-Bates Communicative Development Inventories (CDIs) are frequently used to study communicative skills of children under 3 years of age. Less is known about the usability of such reports for assessing communication skills in older children due to their advanced language skills, and a higher variety of communicative partners and communication contexts. Aims To assess the concurrent and predictive validity of the Estonian (E) CDI-III at ages 3;0 and 4;0 years. The first research goal was to examine its concurrent variability—associations with teacher reports and directly measured language skills. The second goal of the study was to investigate the predictive validity of parent reports—the degree to which parent-and teacher-reported language scores for children at age 3;0 are useful for predicting examiner-administered language comprehension and production scores 1 year later. Methods Estonian monolingual children were investigated longitudinally at ages 3;0 (n = 104; M age = 35.77 months, SD = 0.84; 42% males) and 4;0 (n = 87; M age = 48.18 months, SD = 1.16; 42% males) years. Children were assessed with the parent-reported ECDI-III, with teacher-reported assessments on children’s talkativeness, vocabulary size and grammatical skills, and the examiner-administered New Reynell Developmental Language Scales IV (NRDLS). Results Results indicated significant positive relationships between the ECDI-III total scores, teacher reports, and directly measured language comprehension and production scores, demonstrating concurrent validity of parental reports of children language skills at both ages. When controlling for mothers’ education, children’s gender, and reported language difficulties, parental and teacher reports were predictive of language production scores, whereas only parental reports predicted comprehension scores 1 year later. None of the controls was predictive of later language comprehension and production scores. Conclusion In sum, good concurrent and predictive validity of the ECDI-III shows that the instrument is a valid tool for assessing communicative skills in Estonian children. Results suggest that parent reports can offer useable information also about communicative skills of children older than three years.